PENYULUHAN DAN PENDAMPINGAN PRODUKSI MANDIRI DI ERA PANDEMI KEL. MARGA MULYA, KEC. BEKASI UTARA KOTA BEKASI - Agus Dharmanto; Novita Wahyu Setyawati; Murti Wijayanti; Hasanuddin (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Community service activities that will be carried out are in the form of educating the community through outreach activities regarding COVID-19. The target audience in this Community Service activity are local residents. The implementation of community service is carried out by counseling first and then providing assistance to the practice of the counseling. Availability of experts from Bhayangkara University Lecturers, Bekasi, and assistant staff from students, participants (community), local officials so that this Community Service activity is carried out. The benefits obtained from this Community Service activity include being able to help the community in producing their own Covid-19 prevention media, as well as creative and innovative thinking based on entrepreneurship to be able to support and maintain current conditions.